The Effectiveness Of Anchovy Concentration (Stolephorus insularis) as Antimicrobial to Streptococcus mutans (In Vitro) - Almira Fa’Izah; Istien Wardani; Diana Soesilo (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: Dental and oral diseases which are often found in children is dental caries. Streptococcus mutans is the main cause of caries. Caries can be prevented by using a topical application of fluoride. The Anchovy (Stolephorus insularis) contains protein, vitamins (A, B1, C), and minerals (Fe, Ca, K, F). Calcium fluoride (CaF2) within the anchovy can inhibit the occurrence of dental caries. Purpose: The aim of this study was to determine the antimicrobial ability of anchovy extract (Stolephorus insularis) to Streptococcus mutans. Materials and Methods: This study was a laboratory experimental research with post test only control group design. Diffusion method were applied with 2 controls: negative control used DMSO 1%, positive control used NaF solution, and 3 concentrations of anchovy extract (Stolephorus insularis) 3%, 6%, and 12%, each group were composed of 6 samples. Antimicrobial was assessed by measuring the diameter of the clear zone around the discs contained the anchovy extract (Stolephorus insularis). Data were analyzed by Kruskal-Wallis test followed by Mann-Whitney test. Result: The results from this study showed clear zone around the discs of the anchovy extract (Stolephorus insularis). The more concentration of the extract showed the more antimirobial zone diameter. The average zone of antimicrobial at the concentration of 3% were 7,11 mm, 6% 9,5 mm, 12% 10,78 mm, for the negative control DMSO 1% 6 mm and the positive control NaF solution 8,16 mm. The largest diameter of the clear zone was at concentration of 12% (P < 0,05). Conclusion: The anchovy extract (Stolephorus insularis) had an antimicrobial effect to the growth of Streptococcus mutans.